Functional characterization of the GhNRT2.1e gene reveals its significant role in improving nitrogen use efficiency in Gossypium hirsutum - Zhang,Xinmiao; Feng,Jiajia; Zhao,Ruolin; Cheng,Hailiang; Ashraf,Javaria; Wang,Qiaolian; Lv,Limin; Zhang,Youping; Song,Guoli; Zuo,Dongyun (PeerJ, 2023)
Background Nitrate is the primary type of nitrogen available to plants, which is absorbed and transported by nitrate transporter 2 (NRT2) at low nitrate conditions. Methods Genome-wide identification of NRT2 genes in G. hirsutum was performed. Gene expression patterns were revealed using RNA-seq and qRT-PCR. Gene functions were characterized using overexpression in A. thaliana and silencing in G. hirsutum. Protein interactions were verified by yeast two-hybrid and luciferase complementation imaging (LCI) assays. Results We identified 14, 14, seven, and seven NRT2 proteins in G. hirsutum, G. barbadense, G. raimondii, and G. arboreum. Most NRT2 proteins were predicted in the plasma membrane. The NRT2 genes were classified into four distinct groups through evolutionary relationships, with members of the same group similar in conserved motifs and gene structure. The promoter regions of NRT2 genes included many elements related to growth regulation, phytohormones, and abiotic stresses. Tissue expression pattern results revealed that most GhNRT2 genes were specifically expressed in roots. Under low nitrate conditions, GhNRT2 genes exhibited different expression levels, with GhNRT2.1e being the most up-regulated. Arabidopsis plants overexpressing GhNRT2.1e exhibited increased biomass, nitrogen and nitrate accumulation, nitrogen uptake and utilization efficiency, nitrogen-metabolizing enzyme activity, and amino acid content under low nitrate conditions. In addition, GhNRT2.1e-silenced plants exhibited suppressed nitrate uptake and accumulation, hampered plant growth, affected nitrogen metabolism processes, and reduced tolerance to low nitrate. The results showed that GhNRT2.1e could promote nitrate uptake and transport under low nitrate conditions, thus effectively increasing nitrogen use efficiency (NUE). We found that GhNRT2.1e interacts with GhNAR2.1 by yeast two-hybrid and LCI assays. Discussion Our research lays the foundation to increase NUE and cultivate new cotton varieties with efficient nitrogen use.
Keywords: NRT2; NUE; Gene family; Expression pattern; High-affinity nitrate transporter; Gossypium hirsutum